Herbicide selectivity in herbaceous ornamental gardens of tagetes erecta L. - Queiroz, J. R G [UNESP] (2013)
One of the major problems in landscaping in tropics is weed management. The herbaceous ornamental plant, Tagetes erecta L. (Asteraceae), is very popular for its beautiful flowers which can be used in landscape and also as cut flowers. The increase use of this plant and lack of selective herbicides led to the objective of this study to evaluate the herbicide metribuzin selectivity for this ornamental plant. The experimental design was completely randomized using four treatments (herbicide metribuzin doses: 0, 0.5, 1.0 and 1.5 L ha-1, equivalent to 0, 240, 480 and 720 g ha-1) and five replicates. The herbicide was applied over the seedling of T. erecta as pre-emergence of the weed seeds. Evaluations were performed at 7, 14, 21 and 28 days after application (DAA) by visual analysis of the toxicity symptoms over the ornamental, using the European Weed Research Council (EWRC) scale (1 to 9), where 1 is the total absence of symptoms and 9 to death plants. Polynomial regression statistical analysis was used. It was verified that, from the dose of 1.0 L ha-1, T. erecta plants died by 14 DAA, which the most of them had presented a very strong toxicity symptom; for the 0.5 L ha-1 treatment the plants had survived until 28 DAA. However, most of them already exhibited the high toxicity level, dying at 35 DAA. Thus, metribuzin was not suitable for T. erecta even at the lowest rate tested in this study.